E-Government Implementation and Citizen Satisfaction in Public Administration - Hasiun Budi; Hildawati Hildawati (Westscience Press, 2025)
The implementation of e-government has become a central strategy for improving public administration performance and enhancing citizen satisfaction in Indonesia. This study aims to examine the effect of e-government implementation on citizen satisfaction in public administration. A quantitative research approach was employed using a survey method, with data collected from 300 respondents who have experience using e-government services. The measurement instrument was structured using a five-point Likert scale, capturing key dimensions of e-government implementation, including system quality, information quality, service quality, and accessibility, as well as citizen satisfaction with public services. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25, applying descriptive statistics, reliability and validity tests, and simple linear regression analysis. The results indicate that e-government implementation has a positive and statistically significant effect on citizen satisfaction. The regression analysis shows that e-government implementation explains a substantial proportion of variance in citizen satisfaction, demonstrating that effective digital public services contribute to improved efficiency, convenience, and overall service experience. These findings suggest that strengthening the quality and inclusiveness of e-government initiatives is essential for enhancing public service delivery and citizen trust in public administration in Indonesia.